A formação de professores na perspectiva multicultural: do reconhecimento polissêmico à defesa da perspectiva crítica - André Luiz Sena Mariano (EccoS – Revista Científica)
In this paper is discussed, through literature, the inclusion of multiculturalism in research on teacher education. Established a time frame between the years 2000 to 2006 and elected as a source of data collection, the papers presented at ANPEd and at ENDIPE and the journal articles focused on discussion of multiculturalism. It is possible to point out that there is a polysemy among the selected studies, for example, critical multicultural perspective, the intercultural and postcolonial. It appears that the results of selected texts reveal a more defined around a conservative. Closed emphasizing the importance of critical multiculturalism, especially the concept of frontier identity, and the greater emphasis should be given to what has been done with cultural issues in the training of tutors, rather than restrict the discussions concern alluding to the multiple meanings of multiculturalism.